An Experimental and Theoretical Investigation on Thermal Performance of a Gas-Liquid Thermosyphon Heat Pipe Heat Exchanger in a Semi-Industrial Plant (Iranian Journal of Chemical Engineering)
"> Waste heat recovery is very important, because it not only reduces the expenditure of heat generation, but also it is of high priority in environmental consideration, such as reduction in greenhouse gases. One of the devices used in waste heat recovery is heat pipe heat exchanger. An experimental and theoretical research is carried out to investigate heat performance of an air to water thermosyphon heat pipe heat exchanger according to ε-NTU method. The experiments were done according to the following procedure: cold water with 0.1kg/s flows through the condensation section and hot air in a closed cycle is blown into the evaporation section. A blower with varying frequency of current turns in the mass flow rate between 0.14-0.6 kg/s and a temperature range of 125-225°C. The results of the experiments show that as the ratio of C Ch c rises, the rate of heat transfer goes up. The efficiency of the heat pipe heat exchanger remains constant as the temperature of the hot stream goes up, but the amount of heat transferred increases.